An environmentally friendly material for covering hillsides and land to be developed and a method for its construction

CN122958113APending Publication Date: 2026-10-23HUIZHOU SENLUOKE MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611239540.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]本发明的目的在于针对现有裸露土体防护技术存在的环境污染、防护周期短、水土保持效果差、影响土地复用、施工成本高、破坏原生植被等核心问题,提供一种用于覆盖山坡和待开发土地的环保材料及其施工方法

Benefits of technology

1. 彻底解决传统工艺污染难题,生态环保效益显著。本发明完全替代传统聚乙烯塑料网膜防护模式,从根源上杜绝聚乙烯微塑料残留对土壤、水体的永久性污染问题;材料全部采用无机环保原料,搭配粉煤灰、矿渣粉两大工业固废作为核心辅料,固废利用率高,大幅减少水泥等熟料原料用量,降低生产与施工碳排放,完全符合绿色施工、低碳工程建设标准,对周边生态环境无任何负面影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958113A_ABST
    Figure CN122958113A_ABST
Patent Text Reader

Abstract

The application discloses an environment-friendly material for covering a mountain slope and land to be developed and a construction method thereof, and belongs to the technical field of ecological environment-friendly materials and geotechnical engineering water and soil conservation. The application provides an inorganic solidified spraying material which is low in carbon, environment-friendly, controllable in performance and strong in adaptability. The material takes ordinary cement, fly ash, slag powder and modified polymer as core raw materials, and the mass percentage of each component is as follows: ordinary cement 2%, ordinary fly ash 4%, slag powder 3% and modified polymer 1%, and the balance is water, and inorganic pigments can be added as needed to realize color customization. The application forms a gas-permeable and water-permeable structure with uniform microcracks after spraying and solidification of the material by reasonably proportioning industrial solid waste raw materials and combining with polymer modification technology, so that the material has excellent anti-scouring, weather-resistant and corrosion-resistant performances, can effectively prevent water and soil loss and dust pollution in heavy rain, realizes long-term protection for many years, and guarantees water vapor and air circulation of the soil body and does not affect the growth of original plants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of eco-friendly materials and soil and water conservation in geotechnical engineering, and particularly to an environmentally friendly material for covering hillsides and undeveloped land and its construction method. Background Technology

[0002] With the continuous advancement of infrastructure projects such as urbanization, road and transportation engineering, and mining development, a large number of exposed hillsides, leveled idle land, and slope damage areas are generated during the construction process. These exposed soils are exposed to the natural environment for extended periods, and are highly susceptible to severe soil erosion, dust pollution, and other environmental problems caused by rainwater runoff, wind erosion, and sun weathering. This not only damages the regional ecological environment but may also lead to secondary engineering hazards such as river siltation, slope collapse, and land degradation, making it a key challenge in current ecological environment governance and geotechnical engineering maintenance.

[0003] Currently, the industry's methods for protecting and managing exposed soil are relatively limited. The mainstream protection method is to lay polyethylene plastic mesh. Although this method can cover the soil and block dust and light rain erosion in the short term, and has the advantages of convenient construction and low short-term cost, its long-term drawbacks are extremely prominent. First, polyethylene mesh has extremely poor weather resistance. After long-term exposure to sunlight, rain, and temperature changes, it is prone to aging, cracking, and breakage. The protection cycle is very short, requiring frequent replacement and repeated construction, which consumes a lot of manpower, material resources, and financial resources, significantly increasing the routine management costs of idle land and slopes. Second, the fine polyethylene residue after breakage cannot be naturally degraded and will penetrate into the soil pores and accumulate, causing soil microplastic pollution, damaging soil structure, inhibiting soil microbial activity, and causing permanent and irreversible damage to the land ecology, seriously affecting the subsequent development and reuse of the land and the natural growth of vegetation. Third, polyethylene mesh has strong sealing properties, completely blocking the exchange of water vapor and air between the soil and the outside world, resulting in extremely poor soil permeability and water permeability in the covered area. Water cannot infiltrate, which can easily cause soil water accumulation and softening, and the base collapse. At the same time, it hinders the respiration and growth of native plant roots, completely destroying the regional native ecosystem.

[0004] Traditional concrete curing materials are heavy, hard, and have poor air permeability. They are also cumbersome to construct. After molding, they are too dense and hard, completely solidifying the soil. This not only blocks vegetation growth but also requires large-scale demolition and cleanup for subsequent land reuse. The construction costs are high and the efficiency is low, making them unsuitable for the needs of temporary protection of idle land and long-term soil and water conservation. Although some organic curing materials have air and water permeability, they have poor weather resistance and erosion resistance. They are easily washed away and damaged in heavy rain, resulting in poor protective stability. Moreover, most of them are chemically synthesized materials, which release trace amounts of pollutants and are not environmentally friendly.

[0005] Based on the numerous shortcomings of existing technologies, this invention relies on cement-based inorganic modification technology and combines it with the concept of solid waste resource utilization to propose an environmentally friendly inorganic curing spray material suitable for the protection of bare hillsides and undeveloped land. Through scientific formulation and modification, it solves the industry pain points of traditional polyethylene mesh, such as pollution, easy damage, and obstruction of ecological cycle, as well as the heavy, impermeable, difficult to reuse, and environmentally unfriendly nature of traditional curing materials. Summary of the Invention

[0006] The purpose of this invention is to address the core problems of existing bare soil protection technologies, such as environmental pollution, short protection period, poor soil and water conservation effect, impact on land reuse, high construction cost, and damage to native vegetation, by providing an environmentally friendly material and its construction method for covering hillsides and undeveloped land.

[0007] This invention aims to achieve the following technical objectives: First, to completely replace the traditional polyethylene plastic mesh protection mode, eliminate microplastic soil pollution, and practice the concept of low-carbon and environmentally friendly construction; second, to achieve long-term soil protection, with strong weather resistance and no natural breakage or aging problems, providing stable protection for years after a single construction, significantly reducing land and slope maintenance costs; third, to balance air and water permeability with erosion resistance, ensuring no soil erosion or muddy water flow during heavy rains while not hindering soil moisture exchange or damaging the native plant growth environment; fourth, to achieve controllable material strength, providing basic protective strength after curing to meet the needs of personnel walking, while being easy to break up, eliminating the need for special clearing work for subsequent land development and reuse, and removing construction obstacles; fifth, to maximize the use of industrial solid waste raw materials, reduce material production costs, improve resource utilization, and meet green and low-carbon engineering construction standards; and sixth, to have a simple and efficient construction process, adaptable to large-area slopes and flat land construction, with fast curing speed, short construction cycle, and customizable colors, balancing engineering protection and landscape beautification needs.

[0008] An environmentally friendly material for covering hillsides and undeveloped land comprises the following components by weight percentage: 2% ordinary cement, 4% ordinary fly ash, 3% slag powder, 1% polymer, with the balance being water, and inorganic pigments can be added as needed according to landscape requirements.

[0009] Furthermore, the curing performance of the material is as follows: initial setting in 8-12 hours, final setting in 2-3 days, reaching 50% of the design strength in 3 days, fully meeting the standard in 7-14 days, strength in conventional scenarios <2MPa, and compressive strength in mining scenarios ≥15MPa after 28 days.

[0010] Furthermore, the material is sprayed to a thickness of 2-3 mm, and after curing, uniform fine cracks are formed on the surface, giving it a water-permeable and air-permeable structure.

[0011] Furthermore, the modified polymer is a high-performance water-based polymer emulsion; the inorganic pigment is a weather-resistant and environmentally friendly pigment that can be freely mixed to create different colors.

[0012] Furthermore, the application of the aforementioned environmentally friendly cement-based inorganic curing spray material includes the following application steps: S1. Base surface treatment: Remove loose soil and gravel debris from the construction area, level the base surface and compact it mechanically to ensure that the base surface density is >90%, drain the surface water, and control the slope flatness deviation to not exceed 20mm. S2. Material mixing: Weigh each dry component precisely according to the ratio, add water and modified polymer emulsion, and use a forced mixer to mix for 3-5 minutes until the slurry is uniform and free of lumps. Seal and transport to the construction site, and complete the spraying construction within 2 hours. S3. Spraying application: Use a wet sprayer or special spraying equipment to spray at a uniform speed from the inside out, control the spraying distance to 0.8-1.2m, and the thickness of a single spray to 2-3mm, to ensure full coverage, no missed spraying, and no accumulation. S4. Quality Inspection and Acceptance: The curing strength is tested using a penetration tester, the coating thickness is tested using a thickness gauge, and the uniformity of coverage and surface crack condition are visually inspected. Acceptance is completed after all indicators meet the standards.

[0013] The beneficial effects of this invention are as follows: 1. Completely solves the pollution problems of traditional processes, with significant ecological and environmental benefits. This invention completely replaces the traditional polyethylene plastic mesh protection method, eliminating the permanent pollution of soil and water bodies by polyethylene microplastic residues at the source. All materials are made from inorganic environmentally friendly raw materials, combined with fly ash and slag powder, two major industrial solid wastes, as core auxiliary materials. The utilization rate of solid waste is high, significantly reducing the amount of cement and other clinker raw materials used, reducing carbon emissions during production and construction, fully complying with green construction and low-carbon engineering construction standards, and having no negative impact on the surrounding ecological environment.

[0014] 2. Excellent long-term protective performance, significantly reducing operation and maintenance costs. The material of this invention has extremely strong weather resistance, weathering resistance, and erosion resistance. It does not have problems with natural aging, breakage, or detachment. A single construction can achieve stable protection for many years without the need for frequent replacement and repair. It completely eliminates the cumbersome process of repeated laying and maintenance of traditional mesh, greatly reducing the manpower and material resources invested in the operation and maintenance of idle land and slopes, and significantly reducing the management cost of the entire life cycle of the project.

[0015] 3. Precisely balancing protection and ecological adaptation needs. The solidification material of this invention combines high strength and erosion resistance with excellent air and water permeability. In heavy rain, it can firmly lock in the surface soil, completely preventing soil erosion and muddy water flow, resulting in excellent soil and water conservation. At the same time, the permeable porous structure can ensure normal exchange of water vapor and air in the soil, without suppressing the growth of native plants, thus preserving the original ecosystem of the area to the greatest extent and achieving an organic unity between engineering protection and ecological protection.

[0016] 4. Convenient land reuse with no subsequent construction obstacles. The material of this invention has controllable strength and moderate texture after curing. It will not harden into soil after the protective molding is completed. In the subsequent development, remediation and reuse of the land, there is no need for special demolition and clearing operations. It can be directly mechanically excavated and broken up. The broken material can also be reused as a soil cushion layer, which simplifies the construction process, improves construction efficiency and saves secondary development costs.

[0017] 5. Highly efficient and convenient construction, with wide applicability. This invention adopts mechanized spraying construction, with simple procedures and fast construction speed, and can be adapted to various complex scenarios such as large-area slopes, flat land, exposed soil in mining areas, and roadside slopes; the scientific curing cycle ensures rapid molding and quick achievement of standards, which can effectively shorten the construction cycle, and in some scenarios, it can shorten the construction period by more than 40%; at the same time, it supports multi-color customization, which can meet multiple needs such as engineering protection, ecological restoration, landscaping, and engineering signage, and has extremely high application flexibility.

[0018] 6. Low material cost and high resource utilization rate. This invention extensively reuses industrial solid waste fly ash and slag powder, significantly reducing raw material procurement costs. The formula ratio is scientific and the materials used are simplified. The overall cost is far superior to traditional polymer curing materials and concrete protection materials, and it has extremely high engineering promotion value and economic benefits. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 The following are the on-site conditions on the evening of the day in question and the third day after the heavy rain following the application of the environmentally friendly material of this invention. Figure 2 This is a construction site diagram of the present invention; Figure 3 This is a construction site diagram of Example 1; Figure 4 This is a construction site diagram of Example 2; Figure 5 This is a construction site diagram of Example 3. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0022] An environmentally friendly material for covering hillsides and undeveloped land is mainly composed of cement-based inorganic materials, compounded with industrial solid waste powder, modified polymers and inorganic pigments. The mass percentage ratio of each component is precisely optimized. The specific ratio is as follows: 2% ordinary cement, 4% ordinary fly ash, 3% slag powder, 1% polymer, and the balance is water and inorganic pigments added as needed. Among them, the inorganic pigments are added in appropriate amounts according to the needs of the project landscape and signage, and can be omitted when there is no need for customized appearance.

[0023] 1. Material formulation and functional properties Ordinary cement: As the core cementitious base material, it provides basic bonding strength and molding stability for the cured material, ensuring that the material can quickly set and solidify after spraying, firmly adhering to the soil surface and resisting wind and rain erosion. It is the core guarantee for the molding and protective strength of the material.

[0024] Ordinary fly ash: It belongs to industrial coal combustion solid waste. When added, it can optimize the powder gradation of materials, improve the uniformity and flowability of material spraying, reduce the overall density of materials, and realize the design of lightweight materials. At the same time, it can refine the internal pore structure of the cured material, improve the density and weather resistance of materials while ensuring water and air permeability, reduce shrinkage and cracking defects after molding, realize the resource utilization of solid waste, and reduce carbon emissions.

[0025] Slag powder: a solid waste from the metallurgical industry, possesses excellent micro-aggregate filling effect and secondary hydration activity, which can further optimize the internal structure of the material, improve the corrosion resistance, erosion resistance and long-term stability of the solidified material, and extend the service life of the material; at the same time, it can reduce the amount of cement used, reduce raw material costs, and enhance the low-carbon and environmentally friendly attributes of the material.

[0026] Polymer: High-performance water-based polymer emulsion is used as a modifying additive, which can significantly improve the flexibility, adhesion and ductility of the material, avoid large-area cracking of the cured material due to temperature difference and soil micro-deformation, ensure that uniform and fine cracks are formed on the surface of the material after molding, accurately realize the water and air permeability function, and at the same time improve the adhesion between the material and the soil, preventing peeling and flaking.

[0027] Inorganic pigments: They are weather-resistant, sun-resistant, colorfast, environmentally friendly and non-toxic. Colors can be freely mixed according to the needs of engineering landscape beautification, area identification and ecological adaptation, to meet the visual customization needs of different scenarios, and are suitable for high-value engineering scenarios such as landscape slopes and urban construction sites.

[0028] 2. Core performance parameters of the material This invention achieves multi-dimensional adaptation of material properties to engineering requirements through precise proportioning optimization. The core performance indicators are as follows: Curing cycle: Initial setting is completed 8-12 hours after spraying, which allows for normal foot traffic; final setting is completed in 2-3 days, reaching 50% of the design strength in 3 days, and fully reaching the design strength in 7-14 days. Under standard working conditions, the design strength is >1.5MPa. In special mining area reinforcement scenarios, the compressive strength is ≥15MPa after 28 days. In conventional slope and construction site protection scenarios, the strength is <2MPa, balancing protection stability and subsequent excavation convenience.

[0029] Structural characteristics: After curing, the material surface forms uniform and fine cracks, and the internal pore structure is permeable, which has excellent air and water permeability, allowing the soil to exchange normally with the outside air and rainwater, without water accumulation or soil stagnation; the material is lightweight and thin, with a spray coating thickness of only 2-3mm, and the thickness can be flexibly adjusted according to project needs, making it highly adaptable to construction.

[0030] Weather resistance and protection: The structure is stable after molding, with no natural aging, breakage, or detachment issues. One application can provide long-lasting protection for many years. It has excellent resistance to rain erosion, and the material will not break or fall off under extreme rainfall. It can completely lock in the surface soil, preventing soil erosion and muddy water flow. It has good corrosion resistance and weathering resistance, is suitable for complex outdoor natural environments, and has a long maintenance cycle and low maintenance cost.

[0031] Ecological compatibility: Made entirely of inorganic and environmentally friendly raw materials, with no toxic or harmful substances released, it is naturally compatible with the soil ecosystem and will not cause soil pollution; the breathable and permeable structure does not affect the growth of native plant roots in the soil, preserving the original ecosystem of the area to the greatest extent; the material has moderate strength after solidification, and can be directly mechanically excavated and broken up for subsequent land development and reuse, without the need for special clearing and demolition operations, and there are no construction obstacles. The broken material can be directly used as a soil cushion layer, realizing the secondary utilization of resources.

[0032] 3. Standardized construction methods This invention is accompanied by a proprietary standardized construction process, which is simple, efficient, and suitable for large-scale operations. The specific steps are as follows: (1) Base surface treatment: Thoroughly remove loose soil, gravel and debris and other obstacles from the construction slope and ground. Level the uneven base surface and use mechanical equipment to compact the base surface to ensure that the base surface density is >90%. Before construction, check the water accumulation on the base surface and drain the water completely to ensure that the base surface is dry and clean. Strictly control the flatness deviation of the slope surface to not exceed 20mm to lay the foundation for uniform spraying and firm adhesion of the material.

[0033] (2) Material mixing: Weigh the dry materials such as ordinary cement, fly ash, and slag powder according to the preset mass ratio, put the dry materials into the factory forced mixer, add an appropriate amount of water and polymer emulsion, and continue mixing for 3-5 minutes until the slurry is uniform, without lumps and has uniform fluidity; after mixing, load it into a special tanker and seal it for transport to the construction site to ensure that the slurry is completed within 2 hours to avoid the slurry's initial setting failure.

[0034] (3) Spraying construction: Wet spraying machine or special inorganic material spraying equipment is used for operation. The spraying principle of "from the inside out and uniformly advancing" is followed. The spraying distance is uniformly controlled at 0.8-1.2m, and the thickness of a single spray is controlled at 2-3mm. The construction is carried out at a uniform speed throughout the process to ensure that the construction area is fully covered, the thickness is uniform, there are no missed sprays, and there is no accumulation, so as to ensure the uniform performance of the protective layer after molding.

[0035] 4. Quality Inspection and Acceptance Standards To ensure the quality of the project construction, this invention is equipped with a dedicated quality inspection system. After construction is completed, it must pass multiple dimensions of inspection before it can be accepted: a penetration tester is used to test the strength of the cured protective layer to ensure that the strength meets the design standards of the corresponding scenario; a thickness gauge is used to test the spraying thickness point by point to ensure that the thickness is uniform and meets the standards; a comprehensive visual inspection is conducted to check the uniformity of the protective layer coverage and the regularity of surface cracks, and to ensure that there are no defects such as large-area damage, peeling, or missed spraying. Only after all indicators meet the standards can the project be accepted. Example

[0036] The Hong Kong Central Kowloon Expressway Deep Well Self-Compacting Slope Strengthening Project. This project is a key highway slope reinforcement and protection project, utilizing the DM4 model self-compacting strength strengthening spray material developed in this invention to provide full-coverage spray protection for exposed slopes with deep wells on the highway. During construction, mechanized spraying is highly efficient and fast-forming, resulting in stable material curing and high adhesion. Compared to traditional reinforcement processes, the overall construction cycle is shortened by 40%. After completion, the protective layer has withstood long-term erosion from wind, rain, and vehicle airflow without damage, peeling, or soil erosion, significantly improving slope stability and providing long-lasting and stable protection. Example

[0037] The Sha Tin Slope Soil and Water Conservation Reinforcement Project in Hong Kong. This project covers a total construction area of ​​over 5,000 square meters and is a large-scale soil and water conservation project for exposed mountain slopes. The entire process utilized the environmentally friendly cement-based inorganic curing spray material of this invention. Upon completion, the protective layer exhibits uniform and compliant curing strength, with regular surface cracks and excellent air and water permeability, effectively locking in the slope soil and completely resolving slope erosion and dust pollution problems. The material did not damage the original vegetation on the slope, demonstrating good ecological compatibility and requiring no frequent post-construction maintenance, significantly reducing the area's mountain maintenance costs and successfully achieving multiple objectives of slope reinforcement, soil and water conservation, and ecological protection. Example

[0038] The Sai Kung Clear Water Bay Road Slope Reinforcement Project in Hong Kong. This project is a simplified slope reinforcement project without steel mesh, utilizing the improved DM8F spray coating material of this invention. Relying on the material's excellent bonding strength and erosion resistance, slope stability protection can be achieved without the need for steel mesh reinforcement. This invention's technical solution significantly simplifies the construction process, reduces material and labor input, and substantially saves on project costs and construction time. After completion, the slope protection layer is well-formed, exhibits no quality defects during long-term outdoor service, and demonstrates excellent soil and water conservation and slope reinforcement effects.

[0039] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An environmentally friendly material for covering hillsides and undeveloped land, characterized in that: It includes the following components by weight percentage: 2% ordinary cement, 4% ordinary fly ash, 3% slag powder, 1% polymer, and the balance being water. Inorganic pigments can be added as needed according to landscape requirements.

2. The environmentally friendly material for covering hillsides and undeveloped land according to claim 1, characterized in that, The material's curing performance is as follows: initial setting in 8-12 hours, final setting in 2-3 days, reaching 50% of the design strength in 3 days, and fully meeting the standard in 7-14 days. The strength in conventional scenarios is <2MPa, and the compressive strength in mining scenarios is ≥15MPa after 28 days.

3. The environmentally friendly material for covering hillsides and undeveloped land according to claim 1, characterized in that, The material is sprayed to a thickness of 2-3 mm, and after curing, the surface forms uniform and fine cracks, providing a water-permeable and air-permeable structure.

4. The environmentally friendly material for covering hillsides and undeveloped land according to claim 1, characterized in that, The modified polymer is a high-performance water-based polymer emulsion; the inorganic pigment is a weather-resistant and environmentally friendly pigment that can be freely mixed to create different colors.

5. A construction method for an environmentally friendly material used to cover hillsides and undeveloped land, characterized in that, The application of the environmentally friendly cement-based inorganic curing spray material according to any one of claims 1-4 includes the following application steps: S1. Base surface treatment: Remove loose soil and gravel debris from the construction area, level the base surface and compact it mechanically to ensure that the base surface density is >90%, drain the surface water, and control the slope flatness deviation to not exceed 20mm. S2. Material mixing: Weigh each dry component precisely according to the ratio, add water and modified polymer emulsion, and use a forced mixer to mix for 3-5 minutes until the slurry is uniform and free of lumps. Seal and transport to the construction site, and complete the spraying construction within 2 hours. S3. Spraying application: Use a wet sprayer or special spraying equipment to spray at a uniform speed from the inside out, control the spraying distance to 0.8-1.2m, and the thickness of a single spray to 2-3mm, to ensure full coverage, no missed spraying, and no accumulation. S4. Quality Inspection and Acceptance: The curing strength is tested using a penetration tester, the coating thickness is tested using a thickness gauge, and the uniformity of coverage and surface crack condition are visually inspected. Acceptance is completed after all indicators meet the standards.